Innovation of a Shallot Peeling Machine Based on Appropriate Local Resource Technology to Improve the Production Efficiency of Household Industries - Abdul Salam; Nurhidayanti (Department of Mechanical Engineering, Universitas Andalas, 2026)
Household industries engaged in shallot processing in Kapasa Raya, Makassar, face productivity constraints due to manual peeling methods that are time-consuming and labour-intensive. To address these challenges, an appropriate technology innovation was introduced through the design and implementation of a shallot peeling machine that is simple, ergonomic, and tailored to local needs. The research involved several stages, including field surveys, design using Fusion 360 software, fabrication, assembly, and performance testing. The test results indicated that the optimal parameter combination machine rotation speed of 112 rpm, a capacity of 2.5 kg, and peeling duration of 2 minutes with hot water soaking, was able to achieve an efficiency of up to 37.5 kg/hour. This innovation not only accelerates the peeling process and reduces operator fatigue but also maintains the visual quality of the shallots, thereby enhancing the competitiveness of MSME products. The adoption of this machine has proven to provide significant technical as well as socio-economic impacts for small-scale business operators.